Edukasi Pemberian ASI Eksklusif dan MPASI: Strategi Peningkatan Kesehatan Bayi dan Balita di Desa Makarti-Kutai Kartanegara - Sari, Liliana Devita; Wahyuni, Navviatul Algesta; Nurrahmah, Aulia; Subagiyo, Lambang (ANDIL Mulawarman Journal of Community Engagement, 2024)
ABSTRACT: Stunting in infants and toddlers remains a serious issue in Indonesia, particularly in rural areas such as Desa Makarti, Marangkayu District. One of the main causes of stunting is the lack of public awareness regarding the importance of optimal nutrition during the early stages of a child's life. To address this issue, a community service program was conducted at Posyandu Kartini 2, focusing on nutritional education through exclusive breastfeeding and training in the preparation of complementary feeding (MP-ASI). This program aimed to enhance mothers' understanding of the benefits of exclusive breastfeeding for the first six months and the importance of nutrient-rich MPASI to support the growth of infants and toddlers. Through hands-on training in the preparation of affordable and nutritious MP-ASI using locally available food resources, this initiative is expected to be an effective measure in preventing stunting in the region. Based on the results of the program, it was found that the community service contributed to increasing knowledge about exclusive breastfeeding and empowering mothers with the skills to prepare healthy and nutritious MPASI for their infants and toddlers.